Improving the fat content of foods - Williams, Christine M.; Buttriss, Judith (CRC Press ; Woodhead Pub., 2006)
Annotation As health problems such as obesity, diabetes, and heart disease increase world wide, the food industry has come under fire to improve the nutritional quality of its products, especially the fat content. Summarizing key research, this collection examines both the influence of dietary fats on health and practical strategies for improving the fat content of food. Distinguished editors and an international team of contributors, review the evidence on the links between dietary fats and health. They discuss ways of reducing saturated fatty acids in food, explore how to develop and use PUFAs as functional ingredients, and cover ways of improving the sensory quality of product incorporating modified fats.
Keywords: Food -- Fat content.; Oils and fats, Edible.; Unsaturated fatty acids in human nutrition.; elektronické knihy; electronic books